Authentic Assessment Instrument on Redox Reactions to Assess Students’ Cognitive Skills - Qurratu 'Ainillana; Isana Supiah Yosephine Louise (Jurnal Penelitian Pendidikan IPA, 2024)
Authentic assessment is an assessment approach that enable students to demonstrate in-depth understanding and solve complex problem using systematic thinking skills, but teachers find it difficult to develop due to limited knowledge and time. The aim of this research is to produce an authentic assessment instrument for redox reaction materials; determine the characteristics, quality, and feasibility. The instrument development model used was a combination of Oriondo & Dallo-Antonio with Cohen Swerdlik. The development stages were assessment planning, instrument construction, and product testing. The research subjects were 155 of 10th-grade students from three public high schools in Bukittinggi, selected using random sampling technique. Data collection techniques were tests and non-test, the instruments were open ended questions and validation sheets. The authentic assessment instrument developed criteria are: (1) can assess students’ higher order thinking skills; (2) integrate knowledge with skills and various scientific disciplines; (3) develop 21st century competencies; and (4) involve real or everyday life contexts for cognitive aspect. The trial results were analyzed using the PCM 1-PL approach at IRT using Winstep and Parscale program. The characteristics of the item were stated fit because it met the acceptance requirements for MNSQ, ZSTD, and PT-Measure Correlation and the difficulty is in a relatively good level. The reliability of the instrument was classified as good, with test reliability of 0.72 and item reliability of 0.96.